Novice teachers’ emotional labor: a study of volunteer Chinese teachers in African Confucius Institutes - Wu, Mengying; Yan, Wenle (Frontiers in Psychology, 2025)
IntroductionThis study investigates how volunteer Chinese teachers (VCTs) in African Confucius Institutes navigate emotional labor and examines the emotional rules governing their strategic choices.MethodsThrough semi-structured interviews with 16 VCTs, we identified four categories of emotional rules that shape their emotional labor strategies: professional rules, organizational rules, socio-cultural rules, and personal rules, in descending order of influence.ResultsProfessional rules encompass adherence to language teaching guidelines, native cultural teaching norms, and linguistic proficiency requirements, each demanding significant emotional commitment. Organizational rules emphasize hierarchical respect, conflict avoidance, and cultural ambassadorship, particularly through internalized role identification. Socio-cultural rules reflect adaptation to local cultural norms and conformity to local perceptions of Chinese people, demonstrating the dynamic nature of cultural adaptation. Personal rules emerge from individual teaching experiences and student interactions, reflecting teachers’ unique pedagogical approaches. In response to these rules, teachers employ various emotional labor strategies, including surface acting, deep acting, and expressions of naturally felt emotions, through which they apply techniques such as pretending, disguising, and cognitive restructuring. The findings reveal that novice VCTs often experience stress from professional demands and cultural adaptation, frequently managing these challenges through emotional regulation without adequate institutional support.DiscussionThis study extends emotional labor theory by demonstrating how professional, organizational, sociocultural, and personal emotional rules interact in cross-cultural teaching contexts. The findings suggest that emotional rules are not merely external constraints but are actively interpreted and internalized by teachers through their professional practice. These insights provide valuable guidance for developing targeted support systems to enhance VCTs’ emotional well-being and teaching effectiveness in cross-cultural contexts, particularly through pre-departure cultural sensitivity training and ongoing psychological support services.